Pain Management in a Model of Interstitial Cystitis/Bladder Pain Syndrome by a Vaccinal Strategy - Augé, Céline; Basso, Lilian; Blanpied, Catherine; Vergnolle, Nathalie; Gamé, Xavier; Chabot, Sophie; Lluel, Philippe; Dietrich, Gilles (Frontiers in Pain Research, 2021)
Current analgesic treatments for Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS) are limited. Here, we propose a novel antinociceptive strategy exploiting the opioid-mediated analgesic properties of T lymphocytes to relieve from bladder pain. In a chronic model of IC/BPS in rats, we show that a secondary T cell response against intravesically administered ovalbumin prevents from visceral pain in OVA-primed animals. The analgesic effect is associated with the recruitment of T lymphocytes within the inflamed mucosa and is reversed by naloxone-methiodide, a peripheral opioid receptor antagonist. Similarly, intravesical instillation of BCG or tetanus toxoid antigens in vaccinated rats protects from pain in the same model. We show opioid-dependent analgesic properties of local vaccine antigen recall in a preclinical rat model of chronic cystitis. Since BCG bladder instillation is regularly used in humans (as per anticancer therapy), our results open a new therapeutic positioning for this approach, on a pain management indication for IC/BPS patients.